Evaluation of the quality of services provided by the Polish football clubs - Dzięgiel, Andżelika; Luciński, Łukasz (Quality in Sport, 2015)
Fans are the essence of the sports event and their absence in the stands can negatively affect on the value of events, which are evaluated from the perspective of permanent fans, sponsors and media. The main objective of the study was the assessment of the quality of selected services offered by Polish football clubs. The quality of sports services should be defined as the ability to meet the needs of a particular physical activity. By means of on-line survey method was conducted research, receiving responses from nearly three hundred football fans. The results showed that the fan of football is the man between 21 and 30 years of age with secondary education and gross income below 1600 PLN. The quality of examined the activities carry out by the Polish clubs is judged on passable level. The process of improvement should be start with the team website and the assortment of football souvenirs. Sports organizations in order to attract more permanent fans should realize their marketing efforts by regular research of needs and expectations of fans.